Translation and Historical Stereotypes: The Case of Pedro Cieza de León’s Crónica del Perú - Zaro, Juan (TTR, 2000)
AbstractTranslation and Historical Stereotypes : The Case of Cieza de Leon's Crónica del Perú — The Crónica del Perú (books I and II) by Pedro Cieza de León (1553) is one of the most systematic and objective descriptions of the Spanish conquest of America. It is also one of the best written. The book was first translated into English by Captain John Stevens in 1709, then by Sir Clements R. Markham in 1864 for the Hayklut Society, and finally by Harriet de Onís in 1959. However, none of these translations does justice to Cieza's magnificient work. While the two first translations are full of mistakes, acknowledged and unacknowledged omissions, as pointed out by Diffie, 1936; Bernstein and Diffie, 1937 and Pedro R. León, 1971, the third attempts a conflation of the two books into one, resulting in a confusing edition not devoid of misprints and inaccuracies. This paper attempts to show how the English translations of the Crónica, by way of unfortunate or deliberate manipulations aiming to obliterate the objectivity of Cieza's writing, have contributed to the reinforcement of the stereotypes which shape the "Black Legend" of the Spanish conquest of the New World. Stereotypes that, in the light of examples like this, perhaps need to be redefined.